Heterogeneous Preferences and Demand-Side Lifecycle Theory in Camera Industry: Take 35mm SLR and Medium Format Cameras as Examples - CHOU, YU-CHIEH (2012)
As an essential tool, camera acts as crucial media that assist photographers to complete their photography works or make a record. It is common for general users to use small format cameras in their daily lives. Medium format camera, on the other side, is another camera type with fewer mentioned. Therefore, this dissertation adopts Windrum (2005) approaches in order to retest hypotheses of distinct market niches in both 35mm SLR and medium format cameras. Meanwhile, this research employed demand-side lifecycle theory in order to have alternative explanations to consumer heterogeneous and innovation approaches in the case of camera market.